2019
DOI: 10.1161/jaha.118.010721
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Captopril‐Induced Reduction in Blood Pressure Is Associated With Alterations in Gut‐Brain Axis in the Spontaneously Hypertensive Rat

Abstract: Background We have demonstrated that the antihypertensive effect of the angiotensin‐converting enzyme inhibitor, captopril ( CAP ), is associated with beneficial effects on gut pathology. Coupled with the evidence that CAP exerts prolonged reduction in blood pressure ( BP ) after discontinuation of treatment, we investigate whether persistent beneficial actions of CAP are linked to alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 60 publications
5
39
0
Order By: Relevance
“…Moreover, the beneficial effects of NAC therapy are related to the high abundance of genera Holdemania and Allobaculum. Our results tie well with previous studies showing that Holdemania and Allobaculum abundance was negatively correlated with SBP in SHR [47,48]. Nevertheless, there is still a need to validate above-mentioned microbial markers for hypertension identified in the current study in other hypertensive models.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the beneficial effects of NAC therapy are related to the high abundance of genera Holdemania and Allobaculum. Our results tie well with previous studies showing that Holdemania and Allobaculum abundance was negatively correlated with SBP in SHR [47,48]. Nevertheless, there is still a need to validate above-mentioned microbial markers for hypertension identified in the current study in other hypertensive models.…”
Section: Discussionsupporting
confidence: 93%
“…Abundant evidence has demonstrated an association between gut dysbiosis and hypertension (Li et al, ; Mell et al, ; Sun et al, ; Toral et al, , ; Yang et al, ). Our results are consistent with the main features of dysbiotic microbiota described in SHR (Toral et al, , ; Yang et al, ; Yang et al, ): (a) a reduced richness and diversity, (b) an increased F/B ratio, and (c) a reduction in acetate‐ and propionate‐producing bacteria, with higher proportion of lactate‐producing bacteria. Losartan treatment tended to increase richness and diversity, whereas separated bacteria clusters from SHR towards WKY, normalised F/B ratio, and SCFAs‐producing bacteria.…”
Section: Discussionsupporting
confidence: 92%
“…We have recently described that FMT from WKY to SHR reduced neuroinflammation, sympathetic nervous system activity, and BP (Toral et al, ). In addition, the antihypertensive effect of the ACE inhibitor captopril has sustained influence on the brain–gut axis even after the withdrawal of captopril (Yang et al, ). When we explore the effects of FMT from donors SHR‐losartan to receptors SHR, we found decreased F/B ratio, thus improving gut dysbiosis, and increased the prevalence of acetate‐producing bacteria and those of the genus Bacteroides acidifaciens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that antihypertensive medications may lower BP via effects on the gut microbiota. Captopril (CAP) is an angiotensin‐converting enzyme inhibitor used clinically in antihypertensive applications, and increased Allobaculum levels can maintain a sustained antihypertensive effect even after CAP withdrawal (Yang, et al , ). Ang II receptor blockers, such as candesartan and irbesartan, are also commonly used as antihypertensive medications, and they have been reported to normalize the F/B ratio, preserve Lactobacillus levels and prevent gut microbial disruption (Yisireyili, et al , ; Wu et al , , ) (Table ).…”
Section: Interactions Between the Gut Microbiota And Cvdmentioning
confidence: 99%